2012
DOI: 10.1371/journal.pone.0043665
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the CXCR7/CXCR4/CXCL12 Axis in the Malignant Progression of Human Neuroblastoma

Abstract: Neuroblastoma (NB) is a typical childhood and heterogeneous neoplasm for which efficient targeted therapies for high-risk tumors are not yet identified. The chemokine CXCL12, and its receptors CXCR4 and CXCR7 have been involved in tumor progression and dissemination. While CXCR4 expression is associated to undifferentiated tumors and poor prognosis, the role of CXCR7, the recently identified second CXCL12 receptor, has not yet been elucidated in NB. In this report, CXCR7 and CXCL12 expressions were evaluated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 63 publications
4
58
3
1
Order By: Relevance
“…Consistently it has been reported that CXCR4 and CXCR7 receptors are different in both expression patterns and functional roles in Neuroblastoma (Liberman et al, 2012). These variations were also addressed in meningiomas.…”
Section: Discussionsupporting
confidence: 74%
“…Consistently it has been reported that CXCR4 and CXCR7 receptors are different in both expression patterns and functional roles in Neuroblastoma (Liberman et al, 2012). These variations were also addressed in meningiomas.…”
Section: Discussionsupporting
confidence: 74%
“…Thus, future therapies designed to specifically enhance expression of b-arrestin1 may be able to selectively inhibit CXCR4 cell-surface expression and function in neuroblastoma. Our results additionally suggest that b-arrestin1 expression, together with GRK2, may serve as useful markers in combination with CXCR4 for predicting metastatic risk in neuroblastoma, helping to regulate the migration, proliferation, invasion, and metastasis of neuroblastoma that is dependent on CXCR4 (Raffaghello et al, 2009;Liberman et al, 2012). Other b-arrestin1 binding proteins might also modulate CXCR4 expression and function in neuroblastoma, for example, ESCRT-0, STAM-1, and/or AIP-4 (Bhandari et al, 2007;Malik and Marchese, 2010).…”
Section: Sdf-1 Uses B-arrestin1 and Cxcr4 Structures In Neuroblastomamentioning
confidence: 63%
“…In addition to MYCN gene amplification, DNA ploidy changes, and expression of neurotrophin receptors (Vasudevan et al, 2005;Raffaghello et al, 2009;Huang et al, 2011;Davidoff, 2012), elevated expression of the CXCR4 CXC chemokine receptor is a marker and proposed drug target for high-risk neuroblastoma (Shim et al, 2009). CXCR4 expression is associated with neuroblastoma metastatic growth (Liberman et al, 2012), clinical presentation in bone marrow and liver (Geminder et al, 2001;Russell et al, 2004;Meier et al, 2007;Raffaghello et al, 2009;Zhao et al, 2012), and poor prognosis (Russell et al, 2004). Unfortunately, pharmacological targeting of CXCR4 is complicated by the widespread expression of CXCR4 on normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…67 However, this chemokine has also been associated with cancer progression and tumor metastasis. 68,69 In contrast to the more homeostatic effects of CXCL12a, the majority of the remaining CXC chemokines are considered to be proinflammatory. For example, CXCL8 is not constitutively expressed, but exhibits inducible expression in multiple cell types, including neutrophils, epithelial cells, endothelial cells, fibroblasts, and specific cancer cells, largely in response to proinflammatory stimuli such as TNF-a, IL-1, bacterial products, and thrombin.…”
Section: Chemokine Functionsmentioning
confidence: 99%